Training for Hypertension Control Cadres in Pagar Agung Village, Pagar Agung Health Center Working Area in 2021 - Lusiana; Dodi Aflika Farama; Yeni Elviani (PT FORMOSA CENDEKIA GLOBAL, 2023)
Cadres are an extension of health workers at community health centers as well as First Line Health Care in the community who have an important role, so elderly cadres need to be given the skills and knowledge to deal with health problems that generally occur in the community. This activity aims to provide training for hypertension control cadres in Pagar Agung Village. This activity is carried out through several stages, namely planning, implementation, and evaluation, to determine its effectiveness. Community service activities can be carried out well, and this is supported by good cooperation between the Lahat nursing study program at the Palembang Ministry of Health Poltekkes, the Head of the Pagar Agung Health Center, and the Lahat District Health Office. Participants who attended the Hypertension Control Cadre training were motivated after receiving the training.